EFEKTIFITAS MEDIASI PERKARA PERCERAIAN PASCA PERMA NOMOR 1 TAHUN 2008 DI PENGADILAN AGAMA - Triana Sofiani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2010)
this research is aimed to know the effectiveness of mediation process of divorce cases in Family Court of ex Pekalongan Residence after Perma no. 1 / 2008, the supporting factors of it, and any efforts that have been and will be done by Family Court of ex Pekalongan Residence. The result of this research shows that the mediation process in Family Court has not yet been effective. It is caused by many factors. They are the mediator, both parties, period of time, and infrastructure that have not yet been representative and the accumulation divorce cases. Each Family Court, in fact, have done many efforts to solve the problem, but it still need consciousness, thinking, and responsibility among the Family Courts, between the Family Courts and the High Family Court, and the Supreme Court.